Pasture improvement of marginal lands using annual and perennial legumes - Delgado I.; Ochoa M.J. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
The possibility of improving pastures in marginal lands by sowing wild lucerne ('mielga', Medicago sativa L.) and annual medics ( M. polymorpha L., M. truncatula Gaerten. and M. rigidula All.) was studied on uncultivated land at Ballobar (Huesca) in the 1995-99 period. Six treatments before sowing were applied with or without clearing the vegetation, mechanically or by fire, and with or without cultivation using a chisel cultivator. The establishment of the plants, vegetation cover and phytomass production were recorded. The initial establishment of mielga and annual medics was satisfactory but declined in each successive year, specially medics. Cultivation increased the persistence of mielga but reduced plant cover from 65 per cent to 10 per cent. However, plant cover recovered after four years. Total phytomass was greatly reduced by cultivation and increased by the end of the period. The contribution of mielga and medics to phytomass was negligible.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)